DIAGNOSIS, PREVENTION AND TREATMENT OF ISCHEMIC HEART DISEASES - G. K. Rahmatullayeva; N. Kh. Khudayberganova; Ubaydullayeva M. A. (Web of Journals Publishing, 2025)
This article covers the methods of diagnosis, prevention and treatment of ischemic heart diseases. Ischemic heart diseases are characterized by insufficient blood supply to the heart muscle, which occurs as a result of narrowing of the coronary arteries [4,7,8]. With the help of diagnostic methods, including ECG, echocardiography and coronary angiography detected early. Preventive the desease is measures include healthy eating, physical activity, smoking cessation, and stress management [12,13,14]. Treatment options include medications and surgical procedures. This article reviews aspects of the management of ischemic heart disease effectively [9,10,11].
Keywords: Ischemic heart disease, diagnosis, prevention, treatment, coronary angiography, echocardiography, antiplatelet drugs, statins, CABG, PCI.